2012
DOI: 10.1083/jcb.201106096
|View full text |Cite
|
Sign up to set email alerts
|

The rate of change in Ca2+ concentration controls sperm chemotaxis

Abstract: Sperm navigate in a chemoattractant gradient by translating changes in intracellular calcium concentration over time into changes in curvature of the swimming path.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
81
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(84 citation statements)
references
References 53 publications
3
81
0
Order By: Relevance
“…Successful treatment of accessory gland infection was observed to result in rise in concentrations of inorganic phosphate, calcium and magnesium [11]. Furthermore, inorganic phosphate was higher in asthenozoospermic but lower in azoospermic than in normospermic individuals.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…Successful treatment of accessory gland infection was observed to result in rise in concentrations of inorganic phosphate, calcium and magnesium [11]. Furthermore, inorganic phosphate was higher in asthenozoospermic but lower in azoospermic than in normospermic individuals.…”
Section: Introductionmentioning
confidence: 82%
“…But recent information on the subject called these findings to question. For example Alvarez et al, [11] demonstrated that the sperm continued on a straight course even when calcium was abundant and responds to a change in calcium concentration in a mathematical time derived terms. It was further shown that the rate of calcium ion increase dictates how sharply the sperm turns whereas the path of the subsequent runs depend on the steepness of the calcium decline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For all data, error bars represent mean ± SEM with n = 4-6. Statistical comparisons according to Student's unpaired t test indicated * P < 0.05; ** P < 0.01; *** P < 0.001 versus spermatozoa incubated with 0.1 % DMSO + 10 ng μl −1 of rhZP3 chemotaxis have been reported (Alvarez et al 2012 ;Guerrero et al 2013 ;Ingermann et al 2008 ;Wood et al 2003 ;Wood et al 2007 ).…”
Section: Ca 2+ -Activated CL − Channels (Caccs)mentioning
confidence: 99%
“…SAPs initiate their physiological action on spermatozoa through an increase in cyclic guanosine monophosphate (cGMP) levels (Garbers, 1989;Kaupp et al, 2003), which induces membrane potential (V m ) changes (Galindo et al, 2000;Strünker et al, 2006), leading to increases in intracellular pH (pH i ) and Ca 2+ concentrations ([Ca 2+ ] i ) (Nishigaki et al, 2001;Seifert et al, 2015). Changes in [Ca 2+ ] i in particular play a fundamental role in the regulation of the shape of flagellar beating (Böhmer et al, 2005;Wood et al, 2005), namely, in the process of sperm chemotaxis (Alvarez et al, 2012;Guerrero et al, 2010).…”
Section: Introductionmentioning
confidence: 99%